Peroxiredoxin 3 and oxidative stress in recurrent abortion patients - AL-Hamdani, Israa H; Al-Helaly, Luay A (Vojenské zdravotnické listy, 2023)
The pаthоphysiolоgy of recurrent spontaneous abortion (RSA) has been linked to oxidative stress (OS), which is defined as an imbalance between the formation of oxidants and the antioxidant defense system. The goal of this study was to assess the state of OS in recurrent spontaneous abortion by assessing some of its indicators in order to identify women who are at risk of abortion and enhance their reproductive health. Peroxiredoxin 3 (Prx3), progesterone (P4), glutathione (GSH), uric acid (UA), pеrоxynitritе (ONOO-), and mаlоndialdеhyde (MDA) were measured in 40 healthy non-pregnant (HNP) women, 40 healthy pregnant (HP) women without abortion history, and 21 women with recurrent spontaneous abortion (Have at least ≥ 3 consecutive abortion). All subjects are of reproductive age, with the mother gestational age in the HP and RSA groups being ≤ 20 weeks. According to maternal gestational age, RSA and HP women were separated into two categories (1st & 2nd trimester). According to the findings of this study, Prx3 and GSH levels declined considerably in RSA patients compared to HP and HNP patients, but ONOO- and MDA levels increased statistically significantly in RSA patients compared to HP and HNP groups. However, P4 of RSA was found to be significantly lower in the HP group and much higher in the HNP group. The difference in uric acid levels between the RSA and HP groups was statistically significant, but the difference between the RSA and HNP groups was not.Within the first and second trimesters of pregnancy, the difference between the RSA and HP groups showed statistically significant changes in oxidative stress-related biomarkers, with the exception of uric acid, which showed a non-significant difference between the two groups within the second trimester.Finally, the effect of gestational age within RSA was revealed, with serum Prx3 and P4 showing a significant difference between the first and second stages of pregnancy, whereas other oxidative stress indicators were unaffected by pregnancy length within the RSA group.
Keywords: Oxidative Stress; oxidační stres; Pregnancy; Humans; Blood Chemical Analysis; Female; Irák; oxidancia; lidé; Antioxidants; Peroxiredoxin III; peroxiredoxin III; antioxidancia; ženské pohlaví; habituální potrat; Abortion, Habitual; těhotenství; Iraq; Oxidants; Statistics as Topic; biochemická analýza krve; statistika jako téma